Seroepidemiology of Leishmania infantum in dogs in the city of Porto Alegre, Rio Grande do Sul, Brazil - Teixeira, Mariana Caetano; Stobbe, Neusa Saltiel; Schmidt, Verônica; De Lima, Valéria Marçal Felix [UNESP]; Tartarotti, Ana Luisa; Ramos, Raquel Rocha; De Araujo, Flávio Antônio Pacheco (Universidade Estadual de Londrina, 2016)
Leishmaniosis are zoonoses that present several clinical manifestations in humans and have dogs as their main reservoir in the urban environment. Visceral leishmaniasis (VL) is the most severe form of the parasitosis and has been increasing in Brazil, despite the actions of public health agencies. Until 2002, the State of Rio Grande do Sul (RS) was considered free of human and canine leishmaniasis. The first human case of cutaneous leishmaniasis in RS was recorded in 2003. In 2009, the first autochthonous cases of human VL and canine visceral leishmaniasis (CVL) were confirmed in São Borja, RS, and the occurrence of the insect vector was recorded for the first time in the state. In 2010, the first confirmed case of CVL was reported and seropositive dogs were identified in the city of Porto Alegre, RS. Given the importance of this zoonosis and the difficulties of a reliable diagnosis in dogs, this study aimed to identify epidemiological aspects of CVL in dogs in an area of Porto Alegre where cases of the disease have been reported. A total of 300 blood samples were collected from dogs in this area, which were then tested by the methods of RT-DPP® and ELISA for diagnosis of Leishmania infantum. An epidemiological questionnaire was completed by dog owners, containing aspects related to care of the animals, characteristics of their environment, and their living conditions. We observed that 83% (250/300) of the studied dogs were of mixed breed, 58% (175/300) were female, 78% (238/300) slept outdoors, and 61% (183/300) shared their living quarters with other species. Clinically, we observed that 90% (270/300) of the animals were infested by ectoparasites, 70% (210/300) had dermatopathies, 24% (72/300) presented weight loss and anorexia, and 22% (65/300) had ocular disorders. The results of the two serological tests were 100% concordant for the three seropositive samples (1%), and the remaining 297 (99%) were negative for both tests. We conclude that despite the low prevalence of L. infantum seropositive dogs, conditions in the region are favorable for CVL transmission, creating a risk of VL for the human population in the city of Porto Alegre.
Keywords: Dogs; Porto Alegre; Serologic Diagnosis; Visceral Leishmaniasis